A land without people? The GIScience approach to estimating the population of Ottoman Palestine towards the end of the 19th-century. (April 2022) - Zohar, Motti
Abstract: The question of the nature and extent of population in Ottoman Palestine towards the end of the 19th century (∼1880) remains one of significant implications even today. Using the PEF (Palestine Exploration Fund) maps and employing GIScience (Geographic Information Science) approaches, the mapped settlements were extracted and inspected. Based on the population estimates of the PEF surveyors in the 1870s and on the 1922 census of Palestine carried out by the British Mandate authorities, it is possible to estimate the population size in the permanent settlements appearing on the maps. It was found that 864 settlements existed within the boundaries of the PEF map. Of these, 697 settlements were within the boundaries of Ottoman Palestine, with a population of ∼335, 000. Most of the population was concentrated in the municipal towns while part of it inhabited rural regions in the Galilee, Samaria, and Judea. The coastal plain between Jaffa and Haifa, the Jordan Valley, and the northern Negev were considerably less populated. Highlights: Using GIScience for the analysis of the PEF historical map. Evaluating the population of Palestine in late Ottoman period. Quantitative examination of the spatial settlement pattern in late Ottoman Palestine. Enhancing historical-geography studies by applying GIScience approaches.